Effects of financial liberalization on stock market development, FDI inflows and TFP in selected African countries - Olabisi, Balogun Wakilat (2016)
Under the International Monetary Fund and World Bank structural adjustment reform programs, liberalization was introduced to the developing countries as a means of growing these economies. However, two decades after liberalization, empirical findings of some of the liberalized countries in Sub-Saharan African (SSA) countries show mix results. The study sets out to investigate the long run influence of financial liberalization on stock market development, foreign direct investment (FDI), and total factor productivity (TFP) for seven selected SSA countries for the period 1990-2013. The study employs dynamic panel data analysis to investigate for the influence of liberalization on stock market development, FDI and productivity in the seven selected SSA countries. The techniques of Pooled Mean Group (PMG) and the Mean Group (MG) are employed to determine possible long run relationships among the variables. The direction and effects of liberalization on stock market and FDI, and the effects of these FDI inflows on productivity change is crucial for the development of the nascent economies of the SSA. Findings validate the positive significant impact of stock market liberalization on the development of stock market. Liberalized interest rate however has a long run negative influence on development of stock market although it has a positive effect on FDI. The study thus recommends that the individual SSA economies should set up market-friendly financial policy that would further boost the contribution of liberalization to their economies. More efforts should be made to improve the state of poor institutions in order to enhance FDI in the selected SSA nations in order for foreign investment to have sustained impact on productivity. Steps should be taken to encourage the local citizens to invest in stock market so as to reduce the overbearing influences of foreigners in the stock market.